NOVEL MLANTJARAN KA SASAK: FROM DILLEMATIC TEACHERS TO HUMOROUS ONES - Tingkat, I Nyoman (e-Journal of Linguistics; Vol. 9. Juli 2015 No. 2, 2015)
This article discusses the representation of the image of teachers in the novel entitled Mlantjaran ka Sasak written by Gde Srawana. Using the theory of literary sociology and the theory of representation as the basis of analysis, it was found that teachers were  imaged of being dilemmatic, humanistic idealistic, caring about the Balinese culture, and being humorous. Sociologically, the novel entitled Mlantjaran ka Sasak pictured the life background of the Balinese society during 1930s, indicated by the critical attitude of the intellectuals through I Made Sarati and Ida Ayu Priya, the characters who played a role as teachers, towards the caste feudalism in marriage. Such a critical attitude was expressed in such an inciting way that the ethic and aesthetic values needed to educate society were not neglected.
Keywords: representation, image of teachers, modernity, caste feudalism, gender equality, and self identity